(X-8)(x-20)=180

Simple and best practice solution for (X-8)(x-20)=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X-8)(x-20)=180 equation:


Simplifying
(X + -8)(x + -20) = 180

Reorder the terms:
(-8 + X)(x + -20) = 180

Reorder the terms:
(-8 + X)(-20 + x) = 180

Multiply (-8 + X) * (-20 + x)
(-8(-20 + x) + X(-20 + x)) = 180
((-20 * -8 + x * -8) + X(-20 + x)) = 180
((160 + -8x) + X(-20 + x)) = 180
(160 + -8x + (-20 * X + x * X)) = 180
(160 + -8x + (-20X + xX)) = 180

Reorder the terms:
(160 + -20X + -8x + xX) = 180
(160 + -20X + -8x + xX) = 180

Solving
160 + -20X + -8x + xX = 180

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-160' to each side of the equation.
160 + -20X + -8x + -160 + xX = 180 + -160

Reorder the terms:
160 + -160 + -20X + -8x + xX = 180 + -160

Combine like terms: 160 + -160 = 0
0 + -20X + -8x + xX = 180 + -160
-20X + -8x + xX = 180 + -160

Combine like terms: 180 + -160 = 20
-20X + -8x + xX = 20

Add '8x' to each side of the equation.
-20X + -8x + 8x + xX = 20 + 8x

Combine like terms: -8x + 8x = 0
-20X + 0 + xX = 20 + 8x
-20X + xX = 20 + 8x

Reorder the terms:
-20 + -20X + -8x + xX = 20 + 8x + -20 + -8x

Reorder the terms:
-20 + -20X + -8x + xX = 20 + -20 + 8x + -8x

Combine like terms: 20 + -20 = 0
-20 + -20X + -8x + xX = 0 + 8x + -8x
-20 + -20X + -8x + xX = 8x + -8x

Combine like terms: 8x + -8x = 0
-20 + -20X + -8x + xX = 0

The solution to this equation could not be determined.

See similar equations:

| Y=-4.9(3)*3+17(3)+3.4 | | 8+-6x=-6x+12 | | 5x^2+5x= | | (x^2)(p^2)+xyp-((6)(y^2))=0 | | (12x-4)=(10x+10) | | 8x^2y+36xy-140y=0 | | 15x-(-6x)=(-84) | | (23.89-3x)=14 | | 8-6x=-4x+12 | | 4x+-68+x=40 | | 100x^2+240x+144=0 | | (75x+2600)-(225x-x^2)=0 | | Y=-4.9(3)+17(3)+3.4 | | 8+-6x=-4x+12 | | 5c+10=2c+26 | | 4x^2-48x+54=0 | | -3m+30=6 | | -2x+15=21 | | -9+6=3x | | 6(x+4)-(x+3)=x+1 | | 5xw+16x=0 | | -9=-x+10 | | -3+30=6 | | 60z^3+56z^2-32z=0 | | 14z^4-42z^3+6z^2= | | 4x*-86+x=40 | | 9+4x+7x=75 | | 6-(1+2k)=-(k-1) | | 53a-14=63a+32 | | 9=-x+10 | | 6n-9=39 | | 40=25+20m |

Equations solver categories